A Pilot Intervention to Promote Positive Parenting in Refugees from Syria in Lebanon and Jordan - Lakkis, Najla A.; Osman, Mona H.; Aoude, Lara C.; Maalouf, Cosette J.; Issa, Hanane G.; Issa, Ghassan M. (Frontiers in Psychiatry, 2020)
Background: Early childhood development (ECD) is a crucial milestone that shapes a child’s health, wellbeing, education, and personality. Several factors come into play, and each requires the nurturing care of caregivers. Although the importance of ECD is well understood, the implementation of ECD programs is scarce, especially in poor and vulnerable communities. Objective: to improve parents’ wellbeing, parenting stress levels, parenting behavior and discipline strategies after the implementation of a newly designed parenting intervention. Participants and Setting: Parents from Syria (125 mothers and fathers) in 3 refugee camps in Lebanon and Jordan. Methods: This was a pilot cohort study in which parents’ wellbeing, parenting stress levels, parenting behavior, and discipline strategies were evaluated before and after participating in training in the form of interactive and educational sessions to ameliorate their relations and interactions with their children. Results: By the end of this study, parents’ mental health and wellbeing improved (p<0.001, Cohen’s d: 0.61) and their parenting index score was reduced (p<0.001, Cohen’s d: 1.24). Some of their dysfunctional interactions with their children as well as the perceived difficulties and conduct problems in their children aged 3 to 6 years were also reduced significantly. Conclusion: The intervention used in this study succeeded in improving some aspects of parenting practices and disciplines and in improving the parents’ wellbeing; however, more research is needed to assess its long-term effects on parents and their children. Moreover, some adjustments need to be made in the intervention to be more adapted to the context of refugees and underprivileged communities.